Calcifying odontogenic cyst: a report of two clinical cases - Lagarde Xavier; Sturque Julie; Fenelon Mathilde; Marteau Jean Marie; Fricain Jean Christophe; Catros Sylvain (EDP Sciences, 2019)
Introduction: Cystic maxillary lesions are common. In 1962, Gorlin described a rare cystic form termed the calcifying odontogenic cyst (COC) or Gorlin's cyst. Two cases of this form were treated at Bordeaux University Hospital. Observation: The first case was a 17-year-old patient with mandibular odontoma, which had developed over the previous 6 months. Excision was performed under local anesthesia, and the diagnosis of COC was made following pathological analysis. A 6-month follow-up was planned. The second case was a 62-year-old patient with a post-extraction mandibular lesion, which had been evolving for 1 year. Enucleation under local anesthesia led to the diagnosis of COC. No recurrence was observed after 5 years of follow-up. Discussion: COCs are rare lesions affecting mainly the anterior aspect of the mandible. COCs are usually discovered in unforeseen circumstances, and they can be observed as a clinically painless and well-defined oral deformation. Radiological examination often reveals radiolucent and uniloculated lesions, sometimes associated with radiopaque lesions. Pathological analyses are required for final diagnosis. Management is based on complete excision, more or less associated with marsupialization, and requires an annual clinical radiographic monitoring over the next 5 years. Conclusion: COC are rare lesions, usually asymptomatic, whose treatment is based on complete excision. Clinical and radiological follow-up is necessary until complete reossification is achieved.